An Alternaria Leaf Spot of the Swiss Chard in Tripoli- Libya - Abied, Mohamed. A.; Ghazala, Al-Sadek. M.; Abohliga, Al-Taher. A.; Duzan, Haifa M. (المجلة العلمية لكلية التربية, 2023)
This research was conducted to study the disease incidence (DI%) and disease severity (DS%) of the Swiss Chard disease caused by Alternaria alternata on Swiss Chard crops at four sites of Tripoli; Soq – Aljumma, Al-ghrarat, Al- Harart and An-Nofleen. A total of 100 plant samples were collected during this study. Results showed that percentage of disease incidence and disease severity varies among the surveyed locations. The results also showed that the five selected Beta vulgaris yielded different susceptibility. Barese was the high susceptible to the pathogen in (DI %) and (DS %), under greenhouse condition compared to control, whilst, Orange Fantasia was the lowest susceptible. In addition to that, Fordhook Giant was high susceptible under field conditions, also Celery was less favorable under greenhouse conditions compared to others. Parsley was less favorable under field conditions compared to other hosts tested. Alternaria alternata has a wide host range include all tested plants with different (DI%) and (DS%).